During my time : Florence Edenshaw Davidson, a Haida woman - Blackman, Margaret B. (University of Washington Press : Douglas & McIntyre, 1992)
"This book is the first life history of a Northwest Coast Indian woman. Florence Davidson, daughter of noted Haida carver and chief Charles Edenshaw, was born in 1896. As one of the few living Haida elders knowledgeable bout the culture of a bygone era, she was a fragile link with the past. Living in Masset on the Queen Charlotte Islands, some fifty miles off the northwest coast of British Columbia, Florence Davidson grew up in an era of dramatic change for her people. On of the last Haida women to undergo the traditional puberty seclusion and an arranged marriage, she followed patterns in her life typical of women of her generation.